NADPH Oxidase 2 Regulates NLRP3 Inflammasome Activation in the Brain after Traumatic Brain Injury. (12th July 2017) - Ma, Merry W.; Wang, Jing; Dhandapani, Krishnan M.; Brann, Darrell W.
Abstract : Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. After the initial primary mechanical injury, a complex secondary injury cascade involving oxidative stress and neuroinflammation follows, which may exacerbate the injury and complicate the healing process. NADPH oxidase 2 (NOX2) is a major contributor to oxidative stress in TBI pathology, and inhibition of NOX2 is neuroprotective. The NLRP3 inflammasome can become activated in response to oxidative stress, but little is known about the role of NOX2 in regulating NLRP3 inflammasome activation following TBI. In this study, we utilized NOX2 knockout mice to study the role of NOX2 in mediating NLRP3 inflammasome expression and activation following a controlled cortical impact. Expression of NLRP3 inflammasome components NLRP3 and apoptosis-associated speck-like protein containing a CARD (ASC), as well as its downstream products cleaved caspase-1 and interleukin-1 β (IL-1 β ), was robustly increased in the injured cerebral cortex following TBI. Deletion of NOX2 attenuated the expression, assembly, and activity of the NLRP3 inflammasome via a mechanism that was associated with TXNIP, a sensor of oxidative stress. The results support the notion that NOX2-dependent inflammasome activation contributes to TBI pathology.